Nível de evidenciação de informações sobre o capital humano e a percepção de valor das empresas da BM&FBOVESPA - Lumbieri, Leandro (Universidade do Vale do Rio dos Sinos, 2012)
This thesis aims to investigate the relationship between the level of disclosure of information on human capital and the value perception of the companies listed on BM&FBOVESPA. The study was conducted under the light of the agency theory, which indicates that in an inefficient market, due to the informational asymmetry and greater disclosure would reduce the agency costs. In another perspective, the theory of the cost of the owners, points out that greater disclosure could generate costs for owners. Costs such as loss of market share, as the strategic information becomes public, allowing competing companies reformulate their strategy and conquer markets. The present study differs from any existing research because it uses a new index of BM&FBOVESPA companies which was released on May 2, 2011, called BRASIL AMPLO, with 153 papers with negotiability index of 99%, apart from the fact of not having found any study in Brazil regarding the level of disclosure of human capital and his perception of the market. The method driven by research is the deductive and to meet the goals proposed in this study must be carried out using descriptive research, this research has a quantitative nature and is classified as a documentary research. The sample consists of 21 companies in the period 2004 to 2010, the annual reports were collected from its websites. The construction of the level of disclosure of intangible resources of human capital was developed based on the model proposed by Macagnan (2005). The analysis techniques used were multiple linear regression with panel data.The main result rejects the hypothesis of a direct relationship between the level of voluntary disclosure of human capital and perceived value of companies. This confirms the assumptions of the theory of costs where owners of greater voluntary disclosure of information would cost to owners. Stands out as a contribution to future studies on level of disclosure of human capital, the analysis of the importance of capital for each sector. This is because the perceived value of human capital may vary according to sector.
Keywords: Evidenciação voluntária; Percepção de valor; Capital humano; Voluntary disclosure; Value perception; Human capital; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis